2007
DOI: 10.1161/hypertensionaha.107.091355
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose, an α-Glucosidase Inhibitor, Attenuates Postprandial Hypotension in Autonomic Failure

Abstract: Abstract-Postprandial hypotension is an important clinical condition that predisposes to syncope, falls, angina, and cerebrovascular events. The magnitude of the fall in blood pressure after meals depends on enteric glucose availability. We hypothesized that acarbose, an ␣-glucosidase inhibitor that decreases glucose absorption in the small intestine, would attenuate postprandial hypotension. Acarbose or placebo was given 20 minutes before a standardized meal in 13 patients with postprandial hypotension in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 38 publications
(38 reference statements)
4
59
0
2
Order By: Relevance
“…2 Conversely, gastric "distension" appears to attenuate the postprandial fall in blood pressure. In 8 healthy older subjects, we, like Shibao et al, 1 reported that acarbose (100 mg) attenuated the fall in systolic blood pressure and increase in heart rate induced by oral carbohydrate (100 g of sucrose in 300 mL of water), and, as expected, suppressed postprandial glycemia and insulinemia. 5 Although these effects may be attributable to slowing of the small intestinal digestion of carbohydrate, acarbose also retarded gastric emptying substantially (and, accordingly, both decreased the delivery of nutrients to the small intestine and prolonged gastric distension), although this was only evident Ϸ90 minutes after the drink, whereas the fall in systolic blood pressure was evident well before this time.…”
Section: To the Editorsupporting
confidence: 84%
See 1 more Smart Citation
“…2 Conversely, gastric "distension" appears to attenuate the postprandial fall in blood pressure. In 8 healthy older subjects, we, like Shibao et al, 1 reported that acarbose (100 mg) attenuated the fall in systolic blood pressure and increase in heart rate induced by oral carbohydrate (100 g of sucrose in 300 mL of water), and, as expected, suppressed postprandial glycemia and insulinemia. 5 Although these effects may be attributable to slowing of the small intestinal digestion of carbohydrate, acarbose also retarded gastric emptying substantially (and, accordingly, both decreased the delivery of nutrients to the small intestine and prolonged gastric distension), although this was only evident Ϸ90 minutes after the drink, whereas the fall in systolic blood pressure was evident well before this time.…”
Section: To the Editorsupporting
confidence: 84%
“…We read with interest the article by Shibao et al, 1 who reported that acute administration of acarbose had a substantial, beneficial effect on the hypotensive response to a high-carbohydrate meal in patients with autonomic failure. It was suggested that this effect is mediated, at least in part, by a reduction in the insulinemic response to a meal.…”
Section: To the Editormentioning
confidence: 99%
“…As discussed above, the increased natriuresis observed after food intake is reflective of the "impulse-response pattern" of sodium excretion. The marked post-meal drop in systolic and diastolic BP would be the result of reduced RA levels combined with the secretion of vasodilatory gut peptides, such as neurotensin and insulin (Shibao et al 2007). Note that the decrease in RA and BP could also reflect the predominance of parasympathetic activity during the postprandial state, as described by Kobayashi and Kamiya (1997).…”
Section: Components Of the Renin Cascade Blood Pressure And Urinarymentioning
confidence: 96%
“…Secretion of gut peptides with known vasodilatory action, such as insulin and neurotensin, is part of the cause of the meal-induced decline in BP in humans [15]. In dogs, the mechanism of decline of BP after feeding time may be the same as in humans because the digestion and absorption systems of dogs are analogous to those in humans.…”
mentioning
confidence: 99%